(untitled) (PANGEEA, 2025)
Young people leaving the special protection system are a priority segment of the activity of social work but with many gaps that make it difficult for them to successfully integrate into work and society. The annual assessment of the needs and readiness of young people to leave the protection system is considered a necessity, but there is no time to do it. Through this research it was made possible to carry out a recent mapping of the level of preparation of young people for leaving the centre, and to identify common, concrete and uniform actions to facilitate the process of preparation for adult life after the end of their special protection measure.